Peran Kepemimpinan Sekolah dan Kinerja Guru Bimbingan dan Konseling Terhadap Kesiapan Akademik Studi Lanjut Sekolah Dasar - Adit Kadek Suhardita; I Nyoman Tulis; I Wayan Widana; Maximus Gorky Sembiring (Universitas PGRI Kanjuruhan Malang, 2026)
This study examined the effects of principal leadership and teacher performance on elementary students' academic readiness for junior secondary school as a basis for strengthening learning- and career-related school counseling. Academic readiness was represented by learning achievement. This quantitative ex post facto study used proportional random sampling. Data were collected through principal leadership and teacher performance questionnaires and report-card documentation, then analyzed using multiple linear regression. Principal leadership significantly affected academic readiness (t = 3.143; p = 0.002), as did teacher performance (t = 4.847; p < 0.001). Both variables jointly had a significant effect (F = 36.728; p < 0.001) and explained 46.8% of the variance. The findings highlight the importance of school leadership, teacher performance, and collaboration with school counselors in data-informed transition guidance.